Before the old people & still today : an ethnoarchaeology of Yanyuwa places and narratives of engagement - Kearney, Amanda Joanne (North Melbourne, Vic. : Australian Scholarly Publishing, 2009)
For the author of this book, the Yanyuwa people and their country in the Northern Territory offer an opportunity to explore the politics of the past from the perspective of critical and social theory, which allows for multiple interpretations of the past and presents complex systems of meaning in people's relations to place.
Includes bibliographical references (p. 392-423)
Keywords: Yanyuwa (Australian people); Yanyuwa (Australian people) -- Social life and customs; Aboriginal Australians -- Northern Territory; Ethnoarchaeology -- Northern Territory; Religion - Rites - Ceremonial objects - Stones; Social organisation - Kinship; Sites - Sites of significance; Indigenous knowledge; Archaeology; Language - Sociolinguistics; Yanyuwa / Yanuwa people (N153) (NT SE53-04); Culture - Relationship to place; Indigenous peoples - Pacific - Maori; Religion - Dreaming; McArthur River (North NT SE53-03); Manangoora (North NT SE53-04); Borroloola (North NT SE53-03); Israel; Sir Edward Pellew Islands (NT Gulf Islands SD53-16); Wearyan River (North NT SE53-04); Minngarra Lagoon (North NT SD53-15); Bing Bong (North NT SD53-15); Wuriyala (North NT SE53-04); Palestine